A Mediator Role of Social Media Attitudes on the Relationship of Problematic Internet Use With Social Safeness and Pleasure in Adolescents - Aydoğmuş, Emine Nur Akpınar; YILDIRIM, MELİS SERAY ÖZDEN (Trakya Üniversitesi Sosyal Bilimler Enstitüsü, 2019)
The purposes of this study are to examine whether or not there is a mediatorrole of social media attitudes on the relationship with problematic internet use and socialsafeness and pleasure of adolescents and to lead new studies. 461 high school students whowere educated (9th, 10th, 11th and 12th grades) at high schools located in Erzurum, Turkeyin the 2016 -2017 academic year were enrolled in this study. In order to analysing the data,frequency distribution, t Test, Pearson Product Moment Correlation Coefficient andHierarchical Regression Analyses were used by using SPSS 21.0. In order to collect datafrom the participants “Problematic Internet Usage Scale – Adolescent”, “Social Safenessand Pleasure Scale”, “Social Media Attitudes Scale” and also to get demographicalinformation “Demographical Information Form” were used. At the end of the study, themeaningful mediator role of social media attitudes (sub dimensions are social competenceand need for sharing) on the relationship between problematic internet use and socialsafeness and pleasure on adolescents was seen. Also, there were positive relationshipsbetween social safeness and pleasure and social media attitudes; problematic internet useand social media attitudes. Beside there was a negative relationship between social safenessand pleasure and problematic internet use.

Bu araştırmada, ergenlerdeki sosyal güvende hissetme ve memnuniyet ile problemli internet kullanımı arasındaki ilişkide sosyal medya tutumlarının aracı rolünün incelenmesi ve bu konuda yapılacak yeni çalışmalara yol göstermesi amaçlanmıştır. Araştırmaya 2016- 2017 eğitim öğretim yılında, Erzurum İli, Palandöken İlçesi’nde bulunan liselerin 9.,10.,11. ve 12. sınıflarında öğrenim gören toplam 461 öğrenci katılmıştır. Araştırma verilerinin analizinde, SPSS 21.0 paket programından yararlanılarak frekans dağılımları, t testi, Pearson Momentler Çarpımı Korelasyon ve Hiyerarşik Regresyon Analizleri kullanılmıştır. Bu araştırmada verileri toplamak için “Problemli İnternet Kullanım Ölçeği – Ergen Formu”, “Sosyal Güvende Hissetme ve Memnuniyet Ölçeği”, “Sosyal Medya Tutum Ölçeği” ve ergenlerin demografik özelliklerinin elde edilmesi için “Kişisel Bilgi Formu” kullanılmıştır. Araştırma sonucunda, ergenlerde sosyal güvende hissetme ve memnuniyet ile problemli internet kullanımı arasındaki ilişkide sosyal medya tutumlarının (paylaşım ihtiyacı ve sosyal yetkinlik alt boyutları) aracı rolü olduğu görülmüştür. Ayrıca, sosyal güvende hissetme ve memnuniyet ile problemli internet kullanımı arasında negatif yönde; sosyal medya tutumlarının da hem sosyal güvende hissetme ve memnuniyet ile hem de problemli internet kullanımı ile arasında pozitif yönde ilişkiler saptanmıştır.
Ergenlerde Sosyal Güvende Hissetme ve Memnuniyet ile Problemli İnternet Kullanımı Arasındaki İlişkide Sosyal Medya Tutumlarının Aracılık Rolü
Keywords: Problematic Internet Use; Social Media; Social Safeness and Pleasure